The application of participatory action research to climate change adaptation: a reference guide - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Provides a set of concepts and practical tools for use by Climate Change Adaptation in Africa program grantees working to support stakeholders (communities, government agencies, policy makers) in their efforts to adapt ? or to help others adapt ? climate  change. The Guide nevertheless presents a generic set of concepts and tools that is likely to be of use to others engaged in climate change adaptation research and development efforts in the region, or those working to address other development challenges requiring a multistakeholder learning-by-doing approach.